2014
DOI: 10.5194/nhess-14-219-2014
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of forecasting high streamflows 1–3 months in advance with lagged climate indices in southeast Australia

Abstract: Abstract. Skilful forecasts of high streamflows a month or more in advance are likely to be of considerable benefit to emergency services and the broader community. This is particularly true for mesoscale catchments (< 2000 km 2 ) with little or no seasonal snowmelt, where real-time warning systems are only able to give short notice of impending floods. In this study, we generate forecasts of high streamflows for the coming 1-month and coming 3-month periods using large-scale ocean-atmosphere climate indices a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…A number of data-driven modelling studies have demonstrated that monthly streamflow lagged by 1 month (or more) provided some useful information for forecasting at a 1-month lead time (e.g. Bennett et al, 2014;Humphrey et al, 2016;Yang et al, 2017). This study demonstrates that these benefits also hold when CRR models, rather than data-driven approaches, are used as the forecasting model.…”
Section: Beneficial Impact Of State Updating On Forecast Performancementioning
confidence: 67%
“…A number of data-driven modelling studies have demonstrated that monthly streamflow lagged by 1 month (or more) provided some useful information for forecasting at a 1-month lead time (e.g. Bennett et al, 2014;Humphrey et al, 2016;Yang et al, 2017). This study demonstrates that these benefits also hold when CRR models, rather than data-driven approaches, are used as the forecasting model.…”
Section: Beneficial Impact Of State Updating On Forecast Performancementioning
confidence: 67%
“…addressing issues such as model selection and calibration, observed catchment wetness, lagged and real-time forecasts, uncertainties around extremes, bias correction, requirements for high-resolution rainfall forecasts, integration with communication and response systems -is an active area of research in Australia (e.g. Cuo et al, 2011;Tuteja et al, 2011;Wang et al, 2012;Schepen et al, 2012b).…”
Section: Merging S2s Rainfall Forecasts and Hydrological Forecastsmentioning
confidence: 99%
“…Seasonal streamflow forecasts are provided operationally at around 70 sites across Australia, containing statements advising where the percentage chance of low, near-median or high streamflows may be expected at selected locations and where forecast skill is deemed to be acceptable through forecast verification. Bennett et al (2014) recently focused on forecasting high streamflows in southeast Australia for the next 1-3 months using the BJP modelling system, finding positive forecast skill in 1-month high streamflow forecasts. However, whilst longer-range streamflow forecasts are capable of providing additional information when there is not enough data to make specific flood predictions, they do not provide information about flood class, predicted timing or frequency, severity or extent of flood (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Innovative applications of Bayes's theorem to hydrological forecasting have recently successfully emerged [45][46][47][48]. These applications quantify the uncertainty in post-process deterministic streamflow forecasts [49].…”
Section: Introductionmentioning
confidence: 99%